Peran Da’i Badan Koordinasi Masjid dan Musala (BKMM) dalam Menanamkan Nilai-Nilai Keislaman pada Pemuda di Dusun Danau Raya Desa Persiapan Pinang Raya - Sudirman Hamsina; Faelasup Faelasup; Jumrianah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research explores the comprehension of Islamic values among the youth of Danau Raya hamlet, as well as the roles, challenges, and solutions faced by preachers in cultivating these values. Situated in Pinang Raya village, the study employs a qualitative phenomenological approach. Primary and secondary data were gathered through observation, interviews, and document analysis. Participants included BKMM administrators, preachers, community members, and youth from Danau Raya hamlet. Documentation encompassed books, journals, theses, organizational reports, and photos capturing preacher and youth activities.